Inorganic Nanoparticles for Drug Delivery Systems: Design and Challenges - Dadang Muhammad Hasyim; Miku Fujita; Arnes Yuli Vandika (Yayasan Adra Karima Hubbi, 2024)
Inorganic nanoparticles have gained attention in drug delivery systems due to their unique properties, including high surface area, biocompatibility, and the ability to encapsulate therapeutic agents. These characteristics make them promising candidates for enhancing drug efficacy and targeting. This research aims to explore the design parameters and challenges associated with inorganic nanoparticles in drug delivery applications. The focus is on understanding how modifications in nanoparticle design can optimize performance and address existing limitations. A comprehensive literature review was conducted alongside experimental assessments of various inorganic nanoparticle formulations. Key parameters such as size, surface charge, and drug loading capacity were evaluated to assess their impact on drug delivery efficiency. In vitro studies were performed to analyze drug release profiles and cellular uptake.The findings indicate that specific design modifications significantly influence drug delivery performance. For example, smaller nanoparticles with positive surface charges exhibited enhanced cellular uptake and higher drug loading capacities. However, challenges such as stability, scalability, and regulatory hurdles remain prevalent in the field. Inorganic nanoparticles hold great potential for advancing drug delivery systems, but addressing associated design challenges is crucial. Continued research in this area will facilitate the development of more effective and safer drug delivery solutions, ultimately improving therapeutic outcomes for patients.